2013
DOI: 10.1002/14651858.cd010352
|View full text |Cite
|
Sign up to set email alerts
|

Ciclesonide versus other inhaled corticosteroids for chronic asthma in children

Abstract: Ciclesonide versus other inhaled corticosteroids for chronic asthma in children. Cochrane Database of Systematic Reviews, (2), [010352].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…A Cochrane analysis compared ciclesonide with other ICS for children but was inconclusive. 3 The Cochrane analysis that compared small-particle hydrofluoroalkane-beclomethasone and fluticasone for children with asthma was limited because only 2 studies were found. 2 Robroeks et al 20 reported no difference between 12-week therapy with small-particle beclomethasone or fluticasone in either anti-inflammatory effects or clinical outcomes for 33 children with asthma in a small crossover study, although children at study start had normal lung function and generally well-controlled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane analysis compared ciclesonide with other ICS for children but was inconclusive. 3 The Cochrane analysis that compared small-particle hydrofluoroalkane-beclomethasone and fluticasone for children with asthma was limited because only 2 studies were found. 2 Robroeks et al 20 reported no difference between 12-week therapy with small-particle beclomethasone or fluticasone in either anti-inflammatory effects or clinical outcomes for 33 children with asthma in a small crossover study, although children at study start had normal lung function and generally well-controlled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…These preparations require once-daily dosing which is believed to contribute to better adherence 42. A Cochrane Review, however, was unable to refute or confirm superiority in terms of asthma control, exacerbations or side effects when comparing ciclesonide to budesonide and fluticasone 43. Symbicort as Maintenance And Reliever Therapy (SMART) dosing regimen has been shown to reduce the risk of severe exacerbations in adults with asthma.…”
Section: Severe Asthma Treatmentmentioning
confidence: 99%
“…76,77 Though noted to result in improvement in lung function in adult-based studies, a systematic review of studies children aged 4 to 17 years of age could not demonstrate a significant improvement in asthma symptoms using oncedaily ciclesonide compared to twice-daily budesonide administration (risk ratio [RR] 2.20; 95% confidence interval [CI], 0.75 to 6.43). 78 Moreover, concerns have arisen for dose-and duration-dependent adverse effects of daily ICS therapies on linear growth and bone mineral density. 79 Select studies have explored the use of as needed ICS therapies to minimize these concerns.…”
Section: Assessment and Monitoringmentioning
confidence: 99%